Cognitive response to the display design of auto dealer's advertisement - a study of neuromarketing perspective. - Samsuri, Norlyiana (2016)
Neuromarketing research is different from conventional marketing research as it avoids relying upon subjects self-report. Input from Neuromarketing tools are from processes happening in the brain and therefore eliminated introspection and ego from subject. Marketing communication task is carried through advertising. Advertising is one of the most influential communication tools of promotion. Advertisement costs high revenue and marketing is a very competitive business, advertisers have been trying to understand how advertisement works and to improve advertisement so that it ables to capture customer‟s attention. Effective advertisement that able to capture customer‟s attention would contribute to the selling of product. This study focused on which display design of advertisement that would be able to attract most attention by measuring cognitive response and gaze behaviour. Total of 15 subjects were recruited from USM undergraduate medical students. ERP as a cognitive response during viewing different display designs were recorded. The amplitude and latency of the evoked N100, P200, N200 and P300 ERP components were identified. Amplitude and latency data were analysed using One-way ANOVA test and reaction time was analysed using Independent t-test. Two out of the 15 subjects participated in ERP recording were recruited for Eye Tracking recording that measure the gaze behavioural response to the different display design. The result of the ERP and gaze behaviour showed consistent results that subjects were more (among 19 electrodes sites, mean N100 amplitude is higher in VRG view at 17 sites compared to Neutral [Four scalp sites (Fp2, F4, C4 and T3) significantly and 13 sites insignificantly]) attentive to the display design of Vertex Reared Grouped (VRG) view compared to Neutral and Vertex Frontal Grouped (VFG) view, and more (among 19 electrode sites, mean N100 amplitude is higher in RLG view at 14 sites